FACTORS AFFECTING SEMEN PRODUCTION TRAITS IN HOLSTEIN FREISIAN PUREBRED, HOLSTEIN FREISIAN CROSSBRED AND INDIGENOUS BULLS - Vrinda B. Ambike; R. Venkataramanan; S.M.K. Karthickeyan; K.G. Tirumurugaan; Kaustubh G. Bhave; Jayant Khadse (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Data on 1, 64,962 ejaculates of 486 bulls maintained at BAIF (Bharatiya Agro Industries Foundation) Research Foundation was utilized for this study. Six semen production traits viz. ejaculate volume (EV- ml), sperm concentration (SC- 109/ml), initial sperm motility (ISM- %), post-thaw motility (PTM- %), total number of spermatozoa per ejaculate (TNS- 109/ejaculate) and the theoretical number of semen doses (TNSD) were included in the analysis. Effect of different factors like location, season, year, collection time, collection interval, ejaculation order, breed and age of the bulls was studied on the semen production traits and least-squares means were obtained for these fixed factors while adjusting for the random factors like bull and semen collector. Bayesian method using Gibbs sampling was used to obtain precise least-squares estimates along with 95 per cent posterior standard densities. Better yield was obtained in the early hours of the day before 7 AM, when the ambient temperatures were lower and the first ejaculate was better than the second ejaculate for all the traits. EV was highest when the bulls were six years old, whereas, ISM gradually declined as the age advanced.